Bridging the Gap: Exploring Mental Health Literacy and Help-Seeking Behaviors Among Adolescents in Palu, Indonesia - Andri, Mohamad (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2024)
Adolescent mental health literacy (MHL) is essential for fostering awareness, reducing stigma, and improving help-seeking behaviors. This study explores the barriers and facilitators of MHL among adolescents in Palu, Indonesia, through a qualitative phenomenological approach. Data were collected via in-depth interviews, focus group discussions, and participant observations, analyzed using thematic analysis. Findings reveal that while adolescents recognize mental health as an important aspect of well-being, their knowledge is largely shaped by social media, often leading to misinformation. Structural barriers, including the lack of mental health education in schools and limited access to professional services, exacerbate this issue. Cultural and familial stigmas further discourage open discussions and professional help-seeking. Adolescents primarily seek support from peers rather than professionals due to fear of judgment. To enhance MHL, interventions must integrate school-based education, peer support networks, and digital campaigns promoting evidence-based information. Community-based approaches, including parental education and stigma reduction initiatives, are also necessary. This study contributes to existing literature by providing culturally specific insights into adolescent MHL and suggesting targeted intervention strategies. Future research should focus on evaluating intervention effectiveness in diverse socio-cultural contexts.